Designs of bioreactor systems for solvent-free lipase-catalyzed synthesis of fructose–oleic acid esters - Pyo, Sang-Hyun; Hayes, Douglas G. (JAOCS, Journal of the American Oil Chemists' Society, 2009)
Fructose–oleic acid esters, biodegradable, biocompatible and biobased surfactants and value-added products were synthesized under solvent-free conditions at 65 °C in stirred-batch mode and using several different bioreactor systems. For a stirred-tank bioreactor (STBR) using fed-batch fructose addition and 5.0 wt.% immobilized Rhizomucor miehei lipase (Lipozyme® IM, Novozymes, Franklinton, NC), the conversion yield was over 80%, and the initial rate of the reaction was comparable to previously obtained results using tert-butanol during the initial phase. The bioreactor systems contained a packed “desorption” column (DC) containing fructose crystals and silica gel for delivery of saccharide, and either a STBR or packed-bed bioreactor (PBBR). The liquid stream, initially containing oleic acid and a mixture of fructose–oleic acid esters at a ratio of 75/25 w/w, was continuously recirculated throughout the system …